Kebutuhan Layanan Bimbingan dan Konseling di SMA Negeri 2 Percut Sei Tuan - Abdul Halim; Aryanti Devi Harahap; Muhammad Farhan Dwizar; Riska Rahmadani; Fauziah Nasution (Guidance : Jurnal Bimbingan dan Konseling, 2023)
The purpose of this study was to (1) determine the urgency of the need for guidance and counseling services at SMA Negeri 2 Percut Sei Tuan, (2) to determine the effect after providing services. The problem was found that the level of guidance and counseling service facilities at SMA Negeri 2 still received insufficient attention. So that service and counseling research is important to do, it is also added that his activity has never been carried out at a research location. The research method uses descriptive method with data collection techniques by observation and interviews. The research sample included students in grades X to XI randomly. The results of this study indicate that guidance and counseling service activities have a good effect by finding a large number of enthusiastic students who carry out guidance and counseling services as well as efforts to increase the efforts made by the school in an effort to develop guidance and counseling services in order to support the improvement of guidance and counseling activities that are held.